Successful Mechanical Thrombectomy for Bilateral Anterior Cerebral Artery Occlusions in a Rare Anatomical Variant: A Case Report - Ge B; Zhu J; Zhang F; Han X; Xia Y; Ji Z; Sun P; Li Y; Zhang H; Guo J (International Medical Case Reports Journal)
Beihai Ge,1 Jianjian Zhu,1 Fu Zhang,1 Xianyan Han,1 Yaqian Xia,1 Zeqiang Ji,1 Peili Sun,1 Yuqing Li,1 Huiying Zhang,1 Jianghong Guo2 1Department of Neurology, Rugao Affiliated Hospital of Nantong University, Rugao People’s Hospital, Nantong, Jiangsu, People’s Republic of China; 2Department of Cardiology, Rugao Affiliated Hospital of Nantong University, Rugao People’s Hospital, Nantong, Jiangsu, People’s Republic of ChinaCorrespondence: Jianghong Guo, Department of Cardiology, Rugao Affiliated Hospital of Nantong University, Rugao People’s Hospital, Nantong, Jiangsu, People’s Republic of China, Tel/Fax +86 51387312703, Email jianghongguo123@126.com Beihai Ge, Department of Neurology, Rugao Affiliated Hospital of Nantong University, Rugao People’s Hospital, Nantong, Jiangsu, People’s Republic of China, Tel/Fax +86 51387312703, Email beihaige@126.comBackground: Acute ischemic stroke (AIS) is usually caused by acute occlusion of the cerebral artery. Bilateral anterior cerebral arteries (ACAs) originating from the anterior communicating branch of the same internal carotid artery are a rare anatomical variation in clinical practice. Mechanical thrombectomy (MT) of simultaneous acute occlusion of the bilateral ACAs with this variation has rarely been reported.Case Presentation: A 49-year-old man was referred for sudden onset of right-side weakness and aphasia for almost 55 min. AIS was considered after no bleeding was observed on emergency head computed tomography. Digital subtraction angiography was performed, and bilateral ACAs were found to originate from the anterior communicating branch of the left internal carotid artery and were occluded in their A2 segment. After immediate emergency MT with a stent retriever, the symptoms obviously improved.Conclusion: Simultaneous acute occlusion of the bilateral ACAs originating from the anterior communicating branch of the same internal carotid artery is rare in clinical practice. For such patients, MT with a stent retriever is feasible even if there is a risk of thrombectomy escape, and a stent retriever with aspiration or a direct aspiration technique may be more appropriate.Keywords: acute ischemic stroke, anterior cerebral artery, mechanical thrombectomy, stent retriever, case report